2011
DOI: 10.1111/j.1600-0501.2011.02372.x
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review on survival and success rates of implants placed immediately into fresh extraction sockets after at least 1 year

Abstract: Despite the high survival rate observed, more long-term studies are necessary to determine the success of implant treatment provided immediately after tooth extraction. Special attention has to be given to aesthetic outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

29
396
5
15

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 337 publications
(445 citation statements)
references
References 127 publications
29
396
5
15
Order By: Relevance
“…Therefore, a higher probability of midfacial recession can be expected in immediate implants in the anterior area (Chen & Buser, 2009). Lang et al (2012) have reported that, although major soft tissue changes occur during the first six months after implant placement, they may continue after this period. Interproximal papillae tend to increase with time but midfacially the soft tissue margin rather moves in an apical direction.…”
Section: Hard and Soft Tissue Changes After Immediate Implant Placementmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, a higher probability of midfacial recession can be expected in immediate implants in the anterior area (Chen & Buser, 2009). Lang et al (2012) have reported that, although major soft tissue changes occur during the first six months after implant placement, they may continue after this period. Interproximal papillae tend to increase with time but midfacially the soft tissue margin rather moves in an apical direction.…”
Section: Hard and Soft Tissue Changes After Immediate Implant Placementmentioning
confidence: 99%
“…Lang et al (2012) performed a systematic review that included 2908 immediately placed implants with a mean follow-up of 2 years. The reported survival rate was 98.4% at two years, 97.5% at 3 years.…”
Section: Immediate Implant Placementmentioning
confidence: 99%
“…However, there are also some disadvantages, including the morphology of fresh extraction sockets and the inconsistency between the root anatomy and the shape of the dental implant, resulting in a discrepancy between the socket and the implant bed, which makes it more difficult to achieve primary implant stability. While in traditional implants the stability is provided by the contact of the implant with the newly formed bone in the socket, in immediate implant placement there is a bone defect, and stability can be obtained only by setting the implant in the apical part of the surgical site, in at least 4-5 mm of bone [5][6][7]. Moreover, we must also consider the residual bone defect between the implant and the walls of the socket and the processes of resorption and remodelling that occur after extraction [8].…”
mentioning
confidence: 99%
“…Immediate implant placement (IIP) has some advantages compared with conventional treatment, in which a period between 3 and 6 months should be awaited before implant installation, such as reduced number of surgical procedures, shorter length of treatment, immediate function, potentially lower cost, and fewer restorations. [2][3][4] Although the survival rate observed for IIP is higher than 98% as evidenced in the previous study, 5 particularly attention should be paid to the esthetic outcomes. In the maxillary esthetic region, gingival recession and collapse of the alveolar process is a common complication after IIP due to multiple factors, i.e., thin gingival biotype, loss of buccal bone wall, surgical flap reflection, and delayed crown restoration.…”
Section: Introductionmentioning
confidence: 99%